Perbedaan Kualitas Citra MRI Pelvis Pada Kasus Kanker Prostat dengan Variasi B Value Di Instalasi Radiologi RSUP Prof. Dr. I.G.N.G Ngoerah - Luh Eka Aza Pratiwi; I Made Lana Prasetya; I Putu Sugiartha (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
B value is a factor that reflects the strength and timing of the gradient that will be used to generate a diffusion-weighted image. The higher the b value, the stronger the effect on diffusion. B value can be expressed in units of s/mm2 with a b value range of 500 s/mm2 to 1500 s/mm2. The use of b value in Diffusion Weighted Imaging (DWI) sequences is very important in detecting prostate cancer to distinguish malignant and benign cancer tissue because b value determines the amount of diffusion weighting and shows the sensitivity of the sequence to diffusion. The purpose of this study is to determine the difference in the quality of SNR and CNR images with b value variations in Pelvic MRI examination in prostate cancer cases. This study uses quantitative research methods with an experimental approach. The study population and samples were 4 Pelvic MRI patients with prostate cancer cases who underwent examination in July-August 2023 at the Radiology Installation of Prof.Dr.I.G.N.G Ngoerah Hospital, and each sample was subjected to b value variations of 800, 1000, 1400 and 2000 on the Diffusion Weighted Imaging (DWI) sequence. Data were processed using radiant DICOM and then analyzed using normality test and repeated anova test on SPSS 25 software. The results showed a significance value (p-value) > than 0.05, it can be concluded that H0 is accepted and Ha is rejected, which means that there is no difference in Pelvic MRI image quality in Prostate Cancer Cases with b value variations. The b value variation of 800 on Pelvic MRI examination on Diffusion Weighted Imaging (DWI) sequences with prostate cancer cases can produce more optimal image quality compared to b value variations of 1000, 1400 and 2000.